2013
DOI: 10.1002/ajim.22228
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and suicide: Colorado, 2004–2006

Abstract: Significant differences in means of suicide were seen by occupation, which could guide future suicide prevention interventions that may decrease work-related suicide risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 16 publications
(16 reference statements)
4
54
0
1
Order By: Relevance
“…Previous studies have employed a range of methodologies to study the proposed association between suicide and occupation and, at times, have arrived at different conclusions. For example, although this analysis aligns with another that found high suicide rates among construction workers in Colorado ( 7 ), a meta-analysis using an international occupational classification system found persons in other less-skilled occupations, such as laborers and cleaners, to be at higher risk ( 6 ). …”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have employed a range of methodologies to study the proposed association between suicide and occupation and, at times, have arrived at different conclusions. For example, although this analysis aligns with another that found high suicide rates among construction workers in Colorado ( 7 ), a meta-analysis using an international occupational classification system found persons in other less-skilled occupations, such as laborers and cleaners, to be at higher risk ( 6 ). …”
Section: Discussionsupporting
confidence: 74%
“…Recent studies demonstrated the rate of suicide was highest among persons working in the farming, fishing, and forestry group (84.5/100,000), while the lowest rate was found in the education, training, and library occupational group (7.5/100,000) 64,65. While tick-borne disease exposure could be a contributor to those working in farming and forestry, it might not explain the high rate in fisherman 66.…”
Section: Introductionmentioning
confidence: 99%
“…In South Korea, suicide was the fourth leading cause of death in 2012; it was the most frequent cause of death for individuals in their twenties and thirties and the second most frequent cause of death in those in their forties 1) . Since these age groups reflect the most economically active population, suicide is regarded as a serious social problem.Some investigations on suicide in occupational settings have identified high-risk groups and suggested specific causes and interventions in certain occupations 2,3) . Poor social support, low income and social separation could affect the mental health of manual workers, farmers and miners 4) .…”
mentioning
confidence: 99%
“…Some investigations on suicide in occupational settings have identified high-risk groups and suggested specific causes and interventions in certain occupations 2,3) . Poor social support, low income and social separation could affect the mental health of manual workers, farmers and miners 4) .…”
mentioning
confidence: 99%